The Role of Hyperbaric Oxygen in Head and Neck Reconstruction and Facial Cosmetic Surgery - Tamaki, Akina; Silverman, Dustin A.; Ozer, Enver (Facial Plastic Surgery, 2020)
Hyperbaric oxygen (HBO) is a treatment modality with the primary mechanism of therapy being the delivery of oxygen to hypoxic tissues. A review of HBO applications in the field of head and neck reconstruction and facial cosmetic surgery is provided. HBO can be useful in the management of radiation sequelae and treatment of compromised flaps and grafts. It may also have application in tissue compromise following cosmetic surgery and dermal fillers. We provide evidence from the available literature as well as highlight our experience in using HBO in head and neck reconstruction.
Keywords: hyperbaric oxygen; head and neck reconstruction; facial cosmetic surgery; radiation; graft; flap